Design de moda e design estratégico: análise do deslocamento da técnica de moulage para a etapa metaprojetual - Machado, Luciene (Universidade do Vale do Rio dos Sinos, 2014)
This research proposed an association between draping technique and Strategic Design. Draping, a type of representation in Fashion Design, is a threedimensional modeling technique which consists in directly modeling a piece of fabric on the body or mannequin. It is usually done in the modeling phase, in the end of the design fashion process. The Strategic Design, one type of design, encompasses an earlier design stage, called metaprojetual phase, which consists of research and interpretation of the design problem data that drives to the generation of conceptual proposals, called design concepts. Both Strategic Design and Fashion Design have creative and project character that uses techniques of representation as a way to materialize and visualize their project concepts. The objective of this research was to analyze the effects of the displacement of draping technique to the metaprojetual phase to build design concepts. Through a literature review and with a qualitative exploratory study, it was proposed a Design Exercise developed with the Strategic Design methodology. The exercise consisted of solving a fashion design briefing using the draping technique during the concept building process. It was applied with eight groups, which one consisting of a fashion designer and a designer. Through videos and interviews it was analyzed how they used the draping technique to generate and represent their ideas in the concept building process. The results showed that the draping technique, being used experimentally during the metaprojetual phase, contributed as a stimulus to potentiate the generation and the representation of the designers' ideas as well as it contributed to build, visualize and materialize the design concept.
Keywords: Moulage; Design de moda; Design estratégico; Deslocamento; Geração e representação de ideias; Draping technique; Fashion design; Strategic design; Displacement; Idea generation and idea representation; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial